2013
DOI: 10.1007/s13187-013-0529-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Cancer: Deaf and Hearing Women’s Knowledge Before and After an Educational Video

Abstract: Members of the Deaf community report language and cultural barriers to accessing health information and care. This study evaluated whether an ovarian cancer education video in American Sign Language with English captioning and voiceover could close the anticipated knowledge gap between Deaf and hearing women’s cancer knowledge. Consented Deaf (n = 55) and hearing (n = 52) women’s General, Ovarian, and Total Cancer Knowledge were assessed before and after viewing the video. At baseline, hearing women demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…However, based on the post hoc analysis, it was evident that both message-framed video groups were superior to the lecture-type group in increasing diabetes management knowledge (Table 4). These results support other reports that are published elsewhere (Gazzinelli et al, 2010;Geller et al, 2010;Zossou, Van Mele, Vodouhe, & Wanvoeke, 2010;David & Asamoah, 2011;Cai & Abbott, 2013;Jensen et al, 2013;Wieland et al, 2013;Cusimano, Chipman, Donnelly, & Hutchison, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…However, based on the post hoc analysis, it was evident that both message-framed video groups were superior to the lecture-type group in increasing diabetes management knowledge (Table 4). These results support other reports that are published elsewhere (Gazzinelli et al, 2010;Geller et al, 2010;Zossou, Van Mele, Vodouhe, & Wanvoeke, 2010;David & Asamoah, 2011;Cai & Abbott, 2013;Jensen et al, 2013;Wieland et al, 2013;Cusimano, Chipman, Donnelly, & Hutchison, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The study also provided evidence that, with only a single viewing of the video's testicular cancer components, Deaf men's post-test knowledge scores increased significantly, to the level of equaling or exceeding hearing men's pre-test scores, effectively closing the pre-test knowledge gap between the two groups. This finding is in congruence with past studies that demonstrated the educational value of videos presented in ASL for teaching members of the Deaf community about colorectal [8], prostate [9], testicular [10], cervical [11], breast [12], skin [13], and ovarian [14] cancers.…”
Section: Discussionsupporting
confidence: 91%
“…Although no standards exist for implementing a bilingual approach, there also is no evidence that adapting existing video material developed for a hearing audience by embedding a window with a video of an interpreter signing the information with closed captioning (picture in picture) is an effective way to implement a bilingual approach (2). Rather, this study adds to the growing evidence that ASL-users’ knowledge and satisfaction increases when materials are developed with Deaf community input, ASL discourse is the main point of reference, first-language users sign the material, and supplemental captioning and graphics are included (3-8). …”
Section: Discussionmentioning
confidence: 99%
“…Though none have addressed genetic predispositions, efforts that address language-concordance by accounting for ASL as the first language for many deaf individuals have been found to increase their knowledge regarding a variety of cancers (3-8, 25, 26) and to promote cancer screening behaviors (6). Although conveying health information in ASL is key, these efforts also have included visual images and graphics and English language elements such as captioning or English text.…”
Section: Introductionmentioning
confidence: 99%